2019
DOI: 10.31234/osf.io/gdjtm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Children eat more food when they prepare it themselves

Abstract: Data file for manuscript review. Includes data and variable names. Race and income have been omitted for confidentiality but will be made available upon request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…This was in line with lower daily calorie intake among children from all weight status and specifically in the overweight/obese subgroup as well 40 . However, it was recently demonstrated that children had an increased intake of both healthy and unhealthy foods after the hands‐on meal preparation session, depending on the foods prepared during the session 46 . This highlights the importance of engaging children in preparing healthy meals to improve eating practices, not merely in preparing unhealthy meals.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This was in line with lower daily calorie intake among children from all weight status and specifically in the overweight/obese subgroup as well 40 . However, it was recently demonstrated that children had an increased intake of both healthy and unhealthy foods after the hands‐on meal preparation session, depending on the foods prepared during the session 46 . This highlights the importance of engaging children in preparing healthy meals to improve eating practices, not merely in preparing unhealthy meals.…”
Section: Discussionmentioning
confidence: 54%
“…40 However, it was recently demonstrated that children had an increased intake of both healthy and unhealthy foods after the hands-on meal preparation session, depending on the foods prepared during the session. 46 This highlights the importance of engaging children in preparing healthy meals to improve eating practices, not merely in preparing unhealthy meals. Furthermore, the studies conducted had limited dietary intake assessment with respect to determining the effect on nutrients and the serving sizes of foods consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Persuading children to eat healthy is again open to multiple, subtle influences. As reviewed earlier, children are more willing to eat a salad if they had prepared it themselves (DeJesus et al., ), reflecting their attention to its origins and history. They are more willing to try a food if it was modeled by an individual that the child sees as “like me” – for example, same age or same gender (Frazier et al., ), reflecting their attention to social categories.…”
Section: Discussionmentioning
confidence: 99%
“…Even preparing one's own food leads children to consume more than another, equivalent food that was prepared by someone else (DeJesus, Gelman, Herold, & Lumeng, ). For example, in the study by DeJesus et al., parents brought children into lab where a researcher read aloud instructions for how to prepare a food by combining a set of prepared ingredients (e.g., for making a salad, children individually added into a bow: chopped romaine lettuce, shredded carrots, cooked peas, croutons, and ranch dressing).…”
Section: Implications For Object Valuementioning
confidence: 99%
See 1 more Smart Citation